Dynamics of the World and Russian Economy in the Coronavirus Pandemic Context - Irina A. KATSYUBA; Elena N. KLOCHKOVA; Julia N. LVOVA; Nadezhda P. RADKOVSKAYA; Julia A. STEPKINA (Communications of International Proceedings, 2020)
The article considers and systematizes the main prerequisites for the emergence of the global economic crisis in 2020. A comparative analysis of the crisis of 2008 and 2020 is carried out. The article describes the economic situation in Russia on the eve of the crisis in 2020, by taking into account national characteristics and geopolitical factors in the form of international sanctions which affect its development. The assessment of measures of state support to the Russian economy during the crisis is given. There are defined and well thought out the principles of companies' and corporations' activity in the current conditions.
Keywords: Coronavirus Pandemic; Financial Market; Economy; Financial Crisis.